THE IMPACT EVALUATION OF THE DETAILED SPATIAL PLANNING (DSP) ON ECONOMIC DEVELOPMENT OF THE DISTRICTS IN INDONESIA - Sakti Prabowo (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This study explores the impact of the spatial planning policy reforms, which is the promulgation of Detailed Spatial Planning (DSP) by local government on the economic performance of the districts in Indonesia. It is assumed that districts with the DSP enaction may have better opportunities to achieve higher GDP per capita as the policy reform may give the assurance for the permitted use of space for investors, and thus can contribute to the ease of doing business and investment. The study employs the Fix Effect Difference in Difference (FE DID) Method to explore the impacts of the DSP promulgation. The result suggests that the DSP promulgation may have positive impacts on the economic outcomes of districts in Indonesia, but not significant. A plausible argument is that it is a transition period, thus Indonesia still may face challenges in the implementation of the policy reform. However, heterogeneity analysis shows that in the Kabupaten districts, the DSP promulgation has significant positive impacts on economic development, while the impact is insignificant in the Kota subgroups. This may indicate that the Kabupaten districts may have higher marginal impacts than the Kota districts due to some factors such as land availability.